Improving patient care in the emergency department in a selected hospital: a study on patient centered care - Cardoza, Shyni; Moras, Jyothi Seema (International Journal Of Community Medicine And Public Health, 2024)
Background: Patient-centred care is founded on the principle of active patient and family engagement at all levels of care, enabling them to take ownership of treatment decisions. As patients are best positioned to understand their unique needs and priorities, their involvement is crucial. This study seeks to evaluate the patient centered care delivered by the healthcare providers, specifically doctors and nurses in the emergency department setting. Methods: A Questionnaire-based method was employed to collect data from a sample of 72 patients in the emergency department, assessing patient centered care in the selected tertiary care teaching hospital. The study was conducted between 1st May 2023 to 31st May 2023. Results: The study revealed that patients rated their care experience as very good, achieving high ratings across various dimensions, with the following mean and standard deviation scores: “Patient preference” 4.06±1.13, “Physical comforts” 3.99±1.04, “Coordination of care” 4.03±1.06. “Information and education” 4.08 ±1.06, “Communication” 4.06±1.07, with respect to “Continuity and Transition” 4.13±1.07 and “Family and Friends” 4.24±1.08. These ratings demonstrate a high level of satisfaction with care quality. Conclusions: Patient centered care is a healthcare approach that prioritizes patient needs and values. Its about working together with patients to provide flexible and personalized care. This study found that emergency department staff understand the importance of patient centered care and its benefit for patients and healthcare organisations.